PROSPECTS OF RELATIONS OF UZBEKISTAN AND AZERBAIJAN: NEW HORIZONS OF COOPERATION - Nuridinov Turdali Qambarovic; Islamov Abdulaziz Latif son (Web of Journals Publishing, 2024)
This article analyzes the current and future directions of cooperation between the states of Uzbekistan and Azerbaijan. The dynamics of the development of bilateral relations in the political, economic, transport-logistics and cultural-humanitarian spheres and future opportunities are studied on the basis of a scientific approach.
Keywords: Uzbekistan, Azerbaijan, economic cooperation, political relations, transport-Logistics , TURKPA, cultural cooperation, strategic partnership.